Optimalisasi Pemanfaatan Rapor Pendidikan Untuk Peningkatan Mutu Pendidikan - Gamar Al Haddar Gamar; Annisa Qomariah Annisa; Agustinus Bernadinus Pati Agustinus (BEduManagers Journal : Borneo Educational Management and Research Journal, 2026)
This study aims to analyze the use of the Education Report Card as a Data-Based Planning (PBD) instrument in efforts to improve the quality of education at SDN 006 Samarinda Ulu. The study used a descriptive qualitative approach with data collection techniques through in-depth interviews with the principal and analysis of the 2025 Education Report Card document. The results indicate that the Education Report Card has been systematically utilized as a basis for developing school programs, decision-making, the preparation of the Annual Work Plan, the Medium-Term Work Plan, and school budget management. Although the learning quality indicator is considered good (a score of 74.14), literacy and numeracy achievement remains a major challenge: numeracy is in the moderate category, with 66.67% of students achieving minimum competency, but the numeracy score is only 48.56 (lower-middle). The school's strategy includes improving teacher competency through the Teacher and Education Personnel Center (BGTK), data-based learning reflection, and determining program priorities. The findings indicate that optimal utilization of the Education Report Card strengthens a culture of data-driven decision-making and encourages continuous improvement in education quality.